Intellectual and neurological functioning in Morquio syndrome (MPS IVa). Issue 2 (10th January 2012) - Davison, J. E.; Kearney, S.; Horton, J.; Foster, K.; Peet, A. C.; Hendriksz, C. J.
Abstract: Mucopolysaccharidosis type IVa (MPS IVa, Morquio syndrome OMIM #253000) is a lysosomal storage disease caused by deficiency in N‐acetylgalactosamine‐6‐sulfatase (GALNS, EC 3.1.6.4; encoded by GALNS gene at 16q24.3). Unlike other MPS disorders involving excessive heparan and dermatan sulfate, Morquio syndrome has not been associated with neurological involvement nor with intellectual impairment as this disorder of keratan sulfate has been described as a purely visceral and skeletal disorder. Neurocognitive assessment was undertaken of MPS IVa patients with age appropriate intellectual tests as well as a Child Behaviour Checklist as part of clinical follow up. Available neuroimaging studies (MRI and MR spectroscopy) were reviewed. Whilst more than half of the overall IQ scores fell in the average range, scores for 3/8 children fell below average. A number of behavioural problems were highlighted, including anxiety/depression, attention and somatic complaints. Subtle neuroimaging abnormalities were demonstrated in over half of the children. These findings present a challenge to existing assumptions about the nature of Morquio A syndrome. A hypothesis regarding the potential role of calcium signalling is explored.